Estudo da atividade citotóxica da alfa-lapachona e seu derivado tetrahidropirano - Santos, Evelyne Alves dos (2012)
Quinone metabolites are widely distributed in nature showing various pharmacological activities of clinical importance. The naphthoquinone α-lapachone has been shown to be suitable as a prototype for the development of substances with anticancer properties, as reported by our group to tetrahydropyran derivative (THP), which demonstrated significant cytotoxicity and selectivity against MDA-MB-435 melanoma line. The aim of the present work was to evaluate the mechanism of action involved in the cytotoxicity of α-lapachone and its THP derivative against MDA-MB-435 melanoma cells. Initially, we evaluated the cytotoxicity of α-lapachone and its THP derivative against 8 cell lines, by the MTT assay, showing IC50 of 1.37 and 8.18 µM to breast and melanoma lines, respectively, after 72 hours of incubation. The selectivity of the THP derivative in Alamar Blue assay, demonstrated that THP is 2.6 times less cytotoxic to normal cells as compared to tumor cells. Studies on the mechanism of cell death in MDA-MB-435 tumor line showed that the THP derivative caused a reduction on viable cells associated with an increase of non-viable cells by inducing loss of membrane integrity in concentrations of 5 and 10 µM. The cytotoxic activity of THP was independent of cell cycle, activation of effector caspases and formation of reactive oxygen species, suggesting the occurrence of a necrotic process after 6 hours of treatment, demonstrated by evaluation of membrane integrity. Thus, the data suggest that a tetrahydropyran group introduction in α-lapachone molecule enhances the cytotoxicity of MDA-MB-435 in melanoma cells, via necrosis, which reinforces the importance of naphthoquinones as prototypes for the development of new synthetic compounds with antitumor activity.